2015
DOI: 10.1007/s40171-015-0101-5
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Flexibility Interaction Matrix and Consumer Clusters Preference Criteria in Telecommunication Sector

Abstract: The sequence of various events in Indian Telecom Sector has transformed the industry to become more competitive and dynamic in nature. With increasing competitive levels, the industry calls for more customer centric operations and flexible processes. The emphasis has been laid out in identifying various marketing functions and their use of various flexibility connotations in practise. The interaction matrix between marketing elements and flexibility connotations was developed through Delphi technique, which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 67 publications
2
4
0
Order By: Relevance
“…The study contributes to the existing body of knowledge on the marketing flexibility concept by ascertaining the factors of marketing flexibility and determining the linkages and relationships among them to enhance the flexibility in the marketing operations of Indian telecom service providers. The results and findings are aligned with past studies and literature (Henten et al, 2003;Bourreau & Dog ˘an, 2004;Atasoy, 2013;Sharma et al, 2015;Rajaram & Yadagiri, 2018).…”
Section: Implications and Recommendationssupporting
confidence: 91%
See 1 more Smart Citation
“…The study contributes to the existing body of knowledge on the marketing flexibility concept by ascertaining the factors of marketing flexibility and determining the linkages and relationships among them to enhance the flexibility in the marketing operations of Indian telecom service providers. The results and findings are aligned with past studies and literature (Henten et al, 2003;Bourreau & Dog ˘an, 2004;Atasoy, 2013;Sharma et al, 2015;Rajaram & Yadagiri, 2018).…”
Section: Implications and Recommendationssupporting
confidence: 91%
“…Further moving to explore literature in terms of marketing flexibility in the telecommunications industry, the literature is silent except for only one study on exploring marketing flexibility connotations in the telecommunications sector. The marketing flexibility interaction matrix explored in telecom sectors revealed subjects such as customization, adaptiveness, and localness are mostly used for making the marketing process flexible and customer-oriented (Sharma et al, 2015). They found that flexibility concepts are practiced in the telecom marketing area mainly in advertising, pricing strategies, product planning and development, segmentation, product innovation and differentiation, market research, loyalty program, brand personality, and point of purchase display.…”
Section: Flexibility and Marketing Flexibilitymentioning
confidence: 99%
“…A hassle-free technical backend support and constant improvisation in m-commerce applications are enabling users to experience this phenomenon without any hassle, resulting in enhanced user friendliness toward technology adoption. Whole adoption process of any technology including mobile computing requires flexibility and mobility (Sharma et al , 2015; Shibin et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this digital environment we cannot ignore the increasing influence of information technology and internet penetration on the Indian retail market; this has changed the industry by becoming more competitive and dynamic in nature (Sushil, 2016b). As a gradual increase in competitive levels is transforming the e-commerce platform, the industry is crying out for more customer centric operations and flexible processes (Sharma et al, 2015). In spite of the fact that flexibility is an implicit application of the marketing concept (Sharma et al, 2015), no study has directly addressed online marketing flexibility.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a gradual increase in competitive levels is transforming the e-commerce platform, the industry is crying out for more customer centric operations and flexible processes (Sharma et al, 2015). In spite of the fact that flexibility is an implicit application of the marketing concept (Sharma et al, 2015), no study has directly addressed online marketing flexibility. The key constructs adopted in this study related to online marketing flexibilities are as follow.…”
Section: Literature Reviewmentioning
confidence: 99%